QoG Standard Dataset - Teorell, Jan; Sundström, Aksel; Holmberg, Sören; Rothstein, Bo; Alvarado Pachon, Natalia; Dalli, Cem Mert; Quality of Government Institute, University of Gothenburg (University of Gothenburg, 2013)
The QoG Institute is an independent research institute within the Department of Political Science at the University of Gothenburg. Overall 30 researchers conduct and promote research on the causes, consequences and nature of Good Governance and the Quality of Government - that is, trustworthy, reliable, impartial, uncorrupted and competent government institutions.

The main objective of our research is to address the theoretical and empirical problem of how political institutions of high quality can be created and maintained. A second objective is to study the effects of Quality of Government on a number of policy areas, such as health, the environment, social policy, and poverty.

QoG Standard Dataset is the largest dataset consisting of more than 2,000 variables from sources related to the Quality of Government. The data exist in both time-series (year 1946 and onwards) and cross-section (year 2020). Many of the variables are available in both datasets, but some are not. The datasets draws on a number of freely available data sources related to QoG and its correlates.

In the QoG Standard CS dataset, data from and around 2020 is included. Data from 2020 is prioritized; however, if no data is available for a country for 2020, data for 2021 is included. If no data exists for 2021, data for 2019 is included, and so on up to a maximum of +/- 3 years.

In the QoG Standard TS dataset, data from 1946 and onwards is included and the unit of analysis is country-year (e.g., Sweden-1946, Sweden-1947, etc.).

QoG-institutet är ett oberoende forskningsinstitut som tillhör Statsvetenskapliga institutionen vid Göteborgs universitet. Sammanlagt är det ungefär 30 forskare som bedriver internationell forskning om orsaker till och konsekvenserna av korruption och samhällsstyrningens kvalitet.

Forskningen fokuserar på det teoretiska och empiriska problemet hur politiska institutioner av hög kvalitet kan skapas och upprätthållas, samt studerar effekterna av samhällsstyrningens kvalitet på ett antal olika politikområden, som exempelvis hälsa, miljö, socialpolitik och fattigdom.

QoG Standard Dataset är institutets största datauppsättning som består av mer än 2 000 variabler från källor relaterade till konceptet Quality of Government. Data finns tillgängliga både som tidsserie (från år 1946 till och framåt) och som tvärsnitt (år 2020). De båda dataseten innehåller till stor del samma variabler, men vissa olikheter finns, och bygger på ett stort antal fritt tillgängliga datakällor.

I QoG Standard CS dataset ingår data från omkring 2020. Data från 2020 är prioriterade, men där inga uppgifter finns tillgängliga för 2020 för ett specifikt land så ingår data för 2021. Om inga uppgifter finns tillgängliga för 2021 så ingår data för 2019 och så vidare upp till max +/- 3 år.

I QoG Standard TS dataset ingår data från 1946 och framåt, där analysenheten är land-år (t.ex. Sverige-1946, Sverige-1947, etc.).
QoG Standard Dataset
Keywords: STATE CONTROL; STATLIG STYRNING; POLITICAL INSTITUTIONS; POLITISKA INSTITUTIONER; CORRUPTION; KORRUPTION; DATA; DATA; BUREAUCRACY; BYRÅKRATI; PUBLIC ADMINISTRATION; OFFENTLIG FÖRVALTNING; GOVERNMENT ORGANIZATIONS; STATLIGA ORGANISATIONER; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap